How close are we to curing chronic lymphocytic leukemia? (Hematology Meeting Reports, 2009)
A common introductory statement in discussants of chronic lymphocytic leukemia (CLL) is that it is an indolent disease of older people which is presently “incurable.” At the present time, the question has to be raised as to whether any patients with CLL are being cured. Over the years many hematologic malignancies have been transformed from devastating and uniformly fatal to routinely curable, such as childhood ALL and acute promyelocytic leukemia. The definition of cure is important. Many patients who die of other conditions when in complete remission of their malignancy can be classified as being cured. This may be the situation with CLL.